KALIGRAFI SEBAGAI MEDIA PEMBELAJARAN BAHASA ARAB - Isnaini, Rohmatun Lukluk; Huda, Nurul (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2016)
The art of writing or calligraphy or better known in Arabic as khat has given a touch of art in learning Arabic. This article describes teaching Arabic with calligraphy. This media is proven to be a stimulant and a tool that teachers use to encourage students' interest to learn Arabic. In the learning process as well as in the form of the work, it has made the Arabic and calligraphy into a unity. The model with a touch of calligraphy art is aimed at learners who are just getting to know Arabic to have a sense of joy and affection to learn Arabic. The impact of pleasure can change the mindset of learners that Arabic is easy and fun.